Catheter-Directed Arterial Thrombolysis with a Low-Dose Recombinant Tissue Plasminogen Activator Regimen for Acute Lower Limb Ischemia—Results of the First Regional Registry of Acute Limb Ischemia in Romania - Sorin Barac; Roxana Ramona Onofrei; Octavian Barbu; Stelian Pantea; Cristina Pleșoianu; Ciprian Gîndac; Bogdan Timar; Andreea Luciana Rață (Life)
Acute limb ischemia is a limb-threatening condition that is associated with a high degree of mortality and morbidity, with the latter related to acute kidney injury and rhabdomyolysis that can rapidly lead to multiple organ failure. The aim of this study was to assess the efficacy and safety of catheter-directed arterial thrombolysis in acute lower limb ischemia in the Department of Vascular Surgery, Timișoara, Romania. A total of 158 patients (114 males—72.15% and 44 females—27.85%) with symptoms of acute lower limb ischemia were admitted and treated with catheter-directed arterial thrombolysis following our protocol. The amputation-free survival rate at 1 month after the thrombolysis was 82.3%, and at 6 months it was 77.85%. The performance of additional procedures to obtain distal perfusion was predictive of an improved outcome at 30 days. The estimated survival rate at 6 months was 84.81% (SE 0.02). The mean survival time was 158.74 days. We recommend the usage of a thrombolytic regimen in patients with a life expectancy of more than 6 months, even in Rutherford stage IIb patients, if there is no major impairment in the sensorial and mobility function of the ischemic leg.